2018
DOI: 10.1186/s13018-018-0937-4
|View full text |Cite
|
Sign up to set email alerts
|

Remnant preservation technique versus standard technique for anterior cruciate ligament reconstruction: a meta-analysis of randomized controlled trials

Abstract: BackgroundThis meta-analysis was performed to compare the clinical outcomes of primary anterior cruciate ligament (ACL) reconstruction using the ACL remnant preservation technique versus the standard technique.MethodsPubMed, Embase, and the Cochrane Library were searched through December 24, 2017, to identify randomized controlled studies that compared the use of the ACL remnant preservation technique versus the standard technique for primary ACL reconstruction. Statistical heterogeneity among the trials was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 41 publications
(60 reference statements)
1
37
0
1
Order By: Relevance
“…Yet some studies demonstrated similar rates of cyclops syndrome between remnant- and non–remnant preserving techniques. 3,12,26,40…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet some studies demonstrated similar rates of cyclops syndrome between remnant- and non–remnant preserving techniques. 3,12,26,40…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were no significant differences between techniques in the rate of cyclops lesions. 40 However a major limitation of this meta-analysis was that the included randomized controlled trials reporting this outcome were all small. Consequently, there was only a single case of cyclops syndrome among the pooled population, and the analysis was therefore underpowered to detect a significant difference between remnant preservation and standard techniques with respect to reoperation rates for this particular indication.…”
mentioning
confidence: 99%
“…To consider such an ACL repair, some criteria have to be checked, but the concept highlights the role of the remnant keeping the mechanoreceptors and saving the vascular supply 2 coming from the tibial insertion; this can lead to better graft integration and therefore better clinical results. 6 At the same time, we reported in 2018 good functional and clinical results for ACL reconstruction using 4 strands of semitendinosus autologous graft with both femoral and tibial cortical adjustable fixation. 7 Our technique allows redirection of the proximal end of the remnant, which is not usually healed in femoral ACL native insertions after ACL tear.…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, a recent meta-analysis did not show a true clinically important difference between remnant-preserving and remnant-resecting surgery; therefore, the additional value of remnant preservation is still controversial. 14 The most common complication of remnantpreserving ACL surgery is the increased risk of reoperation for impingement as a result of cyclops lesions from the remnant sagging distally. 15 One of the main benefits of the currently described technique is that the remaining remnant is tensioned and tied over a ligament button at the lateral femoral cortex, thus preventing cyclops lesions.…”
Section: Discussionmentioning
confidence: 99%